N, H and C-atoms Density in Flowing Afterglows of Microwave R/N2-H2 and R/N2-CH4 Discharges with R=N2, He, Ar and Applications to TiO2 Surface Nitriding - Ricard, A.; Amorim , J.; Abdeladim , M.; Sarrette , J. P.; Kim, Y. K. (Plasmas Afterglows with \(N_2\) for Surface Treatments- Edition 2, 2022)
Variations of and -atoms density have been determined along the reduced pressure flowing afterglows of microwave and discharges with , He and Ar. Density of and -atoms and other nitrogen active species such as were obtained from that of -atoms calibrated by titration, using the method of band intensity ratios in several conditions (between early and late afterglows). It has been obtained in addition the density of O-atoms and NO molecules coming from air impurity. It has been deduced the wall destruction probability of and -atoms on the quartz afterglow tube , and . The effects of and -atoms on -atoms inclusion inside surfaces are reported.